Peran Teknologi dalam Meningkatkan Efektivitas Pembelajaran Pendidikan Agama Islam - Fakri (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
In today's digital era, technology has become an integral part of various aspects of life, including in education. Islamic Religious Education (PAI) learning is no exception. This journal aims to explore the role of technology in improving the effectiveness of Islamic Education learning. Through a qualitative approach and analysis of relevant data, this study found that the use of technology, such as online learning applications, learning videos, and social media, can increase student engagement, expand the accessibility of materials, and support more interactive learning. Thus, the application of technology in PAI learning can be an effective strategy to improve the quality of religious education in Indonesia.